Cultural Imperactives of Policy Science - Nanayakkara, Gunapala (My University, 1984)
Policy science is a growing sub-discipline of public administration in the Western developed countries. It advocates a future-oriented and scientific approacch to the improvement of public policy-making processes, policy analysis, policy-making, and policy evaluation. This paper examines some of the culture-bound aspects of policy acience in order to assess its viability and use in developing countries, like Sri Lanka. the writer attempts to whow among other things, that policy science's (a)concern for controlling the future and change presumes a set of orientations in man which is aliem to many LDG cultures, (b) belief in scientific methodology is not quite compatible with the orientation of LDG public administrator, and (c) concern for a policy science culture requires patterns of group behaviours which are not widely practised here. Given the vital role that policy science can play in the LDCs, it is the task for the policy science researchers to find out suitable adjustments within the context of those socio-cultural imperatives.